Open-source planning support system for sustainable regional planning: A case study of Stockholm County, Sweden. (October 2020) - Page, Jessica; Mörtberg, Ulla; Destouni, Georgia; Ferreira, Carla; Näsström, Helena; Kalantari, Zahra
Population increases and environmental degradation are challenges for urban sustainability. Planning support systems are available to assist local authorities in developing strategies toward sustainability and resilience of urban areas, but are not always used in practice. We adapted an open-source planning support system to the case of Stockholm County, Sweden, where there is a productive working relationship between researchers, city planners, and regional planners. We employed a collaborative approach in extending and updating the planning support system and analyzed the outcomes, in order to both improve the planning support system and to investigate the process of planner engagement in planning support system development. The approach involved systematic interactions with local planning authorities and e.g. additional data processing, integrating scientific knowledge, policy, and engagement by planners in the complex process of planning for sustainable urban development. This made the planning support system more user-friendly for local planners, facilitating adoption by planning authorities through overcoming common quality and acceptance barriers to the use of planning support system in practice. Involving planners in planning support system development thus increases (i) planning support system quality, producing relevant and up-to-date outputs, and (ii) acceptance for planning support system by regional planners. Further assessment is required to determine whether planners can operate the adapted planning support system unaided.